Analisis Kebutuhan pada Pembelajaran Kolaboratif sebagai Strategi Pengajaran dalam Kelas Penerjemahan Bahasa Indonesia-Mandarin - Rika Limuria (JLA (Jurnal Lingua Applicata), 2023)
The translator’s profession has existed for decades and evolved as international interaction and communication intensified. The rising demand for the translator’s profession is met by undergraduate-level programs in foreign languages by providing translation classes. One of the challenges in undergraduate-level translation classes is the number of students and the inadequacy of students’ foreign language proficiency. The syllabus design of an undergraduate-level translation classroom has to consider several aspects, such as the number of students, students’ language proficiencies, and students’ needs. Translation class needs to train students in both, hard skills such as translation competence and content knowledge, and soft skills such as working under pressure and teamwork. Collaborative Learning (CL) could be an alternative to tackle this situation. In CL, learners are encouraged to collaborate to produce an acceptable translation. This study investigates the impact of Needs Analysis (NA) and Collaborative Learning (CL) in translation classrooms by surveying students of translation courses. Through NA, the trainer could understand learners’ needs before designing the syllabus. Besides that, CL benefits not only learners’ interpersonal skills but also learners’ translation skills.